Recognition of discrimination: meritocracy and egalitarian primes and their effects on feminist self-identification - Smith, Sara Joanne (Kansas State University, 2009)
Research has shown that a disconnect exists between individuals’ belief in feminist ideology and their willingness to identify as a feminist. Based on this incongruence, research on feminist identification has focused on social-demographic predictors and the thought processes that lead to self-identification. However, not much is known about how the recognition of discrimination is related to feminist self-identification. Research has suggested that part of identifying as a feminist involves the recognition of discrimination. Further, it is suggested that system-justifying ideologies (e.g., meritocracy beliefs) are used to deny the presence of discrimination. The current study further explored this relationship by looking at meritocracy and egalitarian beliefs and how they affected perceptions of discrimination, belief in feminist ideology and identifying as a feminist. Results revealed that participants’ meritocracy and egalitarian beliefs had relatively no effect on their levels of perceived discrimination, belief in feminist ideology or identifying as a feminist.
Keywords: Feminism; Recognition of discrimination; Feminist self-identification; System justifying ideologies; Psychology, Social (0451)